Palmer amaranth (Amaranthus palmeri) control in double-crop dicamba/glyphosate resistant soybean (Glycine max) and dicamba and 2,4-D efficacy on Palmer amaranth and common waterhemp (Amaranthus rudis) - Thompson, Nathaniel Russell (Kansas State University, 2018)
Auxin herbicides have been widely used for broadleaf weed control since the mid-1940’s. With new auxinic herbicide-resistant traits in corn, soybean, and cotton, use of these herbicides is likely to increase. Glyphosate-resistant Palmer amaranth (Amaranthus palmeri) and common waterhemp (Amaranthus rudis) are two primary problematic weed species that will be targeted with dicamba and 2,4-D in the new systems. No-till double-crop soybean after winter wheat harvest is a popular cropping system in central and eastern Kansas, however, management of glyphosate resistant Palmer amaranth has become a serious issue. Field experiments were established near Manhattan and Hutchinson, KS, in 2016 and 2017, to compare seventeen herbicide treatments for control of Palmer amaranth and large crabgrass (Digitaria sanguinalis) in dicamba/glyphosate resistant no-till double-crop soybean after winter wheat. Herbicide programs that included a residual preemergence (PRE) treatment followed by a postemergence (POST) treatment offered greater Palmer amaranth control 8 weeks after planting when compared to PRE-only, POST-only and burndown-only treatments. All treatments that contained glyphosate POST provided complete control of large crabgrass compared to less than 43% control with PRE-only treatments. Soybean grain yield was greater in programs that included PRE followed by POST treatments, compared to PRE-only and burndown-only treatments. A second set of field experiments were established in 2017 near Manhattan and Ottawa, KS to evaluate dicamba and 2,4-D POST efficacy on Palmer amaranth and common waterhemp. Five rates of dicamba (140, 280, 560, 1121, and 2242 g ae ha⁻¹) and 2,4-D (140, 280, 560, 1121, and 2242 g ae ha⁻¹) were used to evaluate control of the Amaranthus spp. Each experiment was conducted twice at each location. Dicamba provided better Palmer amaranth and common waterhemp control than 2,4-D across the rates evaluated. Control of Palmer amaranth was 94% and 99% with dicamba rates of 1121 and 2242 g ae ha⁻¹, respectively, but 2,4-D never provided more than 80% control at any rate. The highest rates of both dicamba and 2,4-D provided greater than 91% common waterhemp control, but control was less than 78% with all other rates of both herbicides. Palmer amaranth and common waterhemp control did not exceed 73% with the highest labelled POST rates of either dicamba or 2,4-D. Auxinic herbicide-resistant traits in corn, soybean, and cotton offer new options for controlling glyphosate-resistant Palmer amaranth and common waterhemp, however proper stewardship is vital to maintain their effectiveness.
Keywords: Amaranth; Double-Crop; Soybean; WaterhempPalmer